Land of Illusion - Lily & Honglei Art Studio (InTensions, 2014)
"Land of Illusion" is a virtual reality project designed to continue and extend the discussion and experiment on creating new cultural expressions with interactive digital multimedia, particularly virtual reality technology. The fundamental concept of Land of Illusion is to construct a symbolic space incorporating image, motion, text and sound to reflect on eastern philosophy. Land of Illusion is also designed as an open forum on the Internet (in Second Life) that enables dialogue focusing on the relationship between cultural heritage and today's society.